2020
DOI: 10.3389/fnsyn.2020.00016
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Presence of Oligomeric Aβ Differentially Modulates Spine Parameters in the Hippocampus and Cortex of Mice With Low APP Transgene Expression

Abstract: Alzheimer's disease is regarded as a synaptopathy with a long presymptomatic phase. Soluble, oligomeric amyloid-β (Aβ) is thought to play a causative role in this disease, which eventually leads to cognitive decline. However, most animal studies have employed mice expressing high levels of the Aβ precursor protein (APP) transgene to drive pathology. Here, to understand how the principal neurons in different brain regions cope with moderate, chronically present levels of Aβ, we employed transgenic mice expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Micrographs (voxel size: 0.06 × 0.06 × 0.30 µm) were blind deconvolved using AutoQuantX vX3.0.5 software (Media Cybernetics Inc., USA) in order to improve the signal-to-noise ratio, and the analysis of individual dendritic spines was carried out using the morphometric software 3DMA v0204 [ 39 ]. The spines were classified into mushroom, stubby and thin based on the ratio of head to neck diameter and the ratio of length to neck diameter as described before [ 40 , 41 ]. Confocal tiles of complete CA1 hippocampal arbors were acquired as previously described [ 42 ] using a Zeiss 510 META NLO confocal laser scanning microscope (Zeiss, Oberkochen, Germany) equipped with a ×40 oil-immersion objective (NA, 1.3) and a Helium/Neon 543 nm laser governed by LSM 510 v4.0 SP2 software.…”
Section: Methodsmentioning
confidence: 99%
“…Micrographs (voxel size: 0.06 × 0.06 × 0.30 µm) were blind deconvolved using AutoQuantX vX3.0.5 software (Media Cybernetics Inc., USA) in order to improve the signal-to-noise ratio, and the analysis of individual dendritic spines was carried out using the morphometric software 3DMA v0204 [ 39 ]. The spines were classified into mushroom, stubby and thin based on the ratio of head to neck diameter and the ratio of length to neck diameter as described before [ 40 , 41 ]. Confocal tiles of complete CA1 hippocampal arbors were acquired as previously described [ 42 ] using a Zeiss 510 META NLO confocal laser scanning microscope (Zeiss, Oberkochen, Germany) equipped with a ×40 oil-immersion objective (NA, 1.3) and a Helium/Neon 543 nm laser governed by LSM 510 v4.0 SP2 software.…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether a negative correlation between tau and α-syn levels also exists under disease conditions, we investigated a possible correlation between the levels of the two proteins in a mouse model of amyloidosis and AD patients. Interestingly, when examining lysates from hemibrains of old mice with chronic amyloidosis (Hrynchak et al, 2020), we observed no decrease in tau protein with age and the negative correlation between tau and α-syn was also absent (Figs. 5A, B).…”
Section: Resultsmentioning
confidence: 91%
“…Indeed, the amyloid peptide Aβ1-42 has been shown to decrease actin dynamics in vitro and reduce the F-actin/G-actin ratio in synaptosomes of APPswe/PS1ΔE9 mice at as early as 1 month of age [ 125 ]. This effect precedes amyloid plaque formation and follows disease progression [ 126 , 127 ]. Aβ oligomers induce the activation of calcineurin, which results in actin depolymerization and subsequent spine dystrophy and eventually loss of actin fibers [ 128 , 129 ].…”
Section: α7 Nachr In Disorders Of the Cnsmentioning
confidence: 99%
“…Deposition of Aβ in plaques would decrease the availability of soluble forms of Aβ, thus precluding signaling towards actin depolymerization in an attempt to protect spine structure. This mechanism may be exhausted at some point in the evolution of the disease and may explain the reduced levels of F-actin measured in synaptosomes from human postmortem brain tissue in Alzheimer patients with mild cognitive impairment [ 125 , 126 ].…”
Section: α7 Nachr In Disorders Of the Cnsmentioning
confidence: 99%